Proposed upgrading of Proton Edar 3S for Proton Sdn. Bhd at Lot 15 Jalan Lahat, 31450 Menglembu, Ipoh, Perak / Nurul Nadia Aziz - Aziz, Nurul Nadia (Faculty of Architecture, Planning and Surveying, 2011)
The final project for student of Diploma Interior Design is a manisfestation towards the student’s knowledge about the whole aspect on interior design that had been learned from basic until the final presentations on the proposed design. The project that had been chosen for the final project is proposed upgrading of Proton Edar 3S for Proton Sdn. Bhd. at Lot 15, Jalan Lahat, Menglembu in Ipoh, Perak Darul Ridzuan . This proposed upgrading the showroom and services for Proton Edar Sdn. Bhd. The upgrading actually for attract the people to elevate Proton product to the international. Hopefully, it can be the pride to Malaysia for the first product in transportation. The concept had been chosen in this proposed is ‘Balance of Function’.